Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2134/agronj2012.0295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drought Probability Assessments Based on Atmospheric Water Deficit and Soil Water Deficit

Abstract: Methods that estimate the probability of agricultural drought using atmospheric data can be widely applied but have not been compared with actual drought occurrence indicated by soil moisture measurements. Our objectives were to develop a drought probability assessment method using long‐term measurements of soil water deficits (SWDs) and to compare the resulting probabilities with those of an existing method based on atmospheric water deficits (AWDs). Fifteen years of daily precipitation, air temperature, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…In line with the results from some previous studies [26,28,36,67,75,76], it was found that the atmospheric conditions over NEB influences the upper soil water balance dynamic. This characteristic is reflected by a moderate coupling strength between the AWD and SWDIS from June 2010 to December 2013 in the entire NEB (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In line with the results from some previous studies [26,28,36,67,75,76], it was found that the atmospheric conditions over NEB influences the upper soil water balance dynamic. This characteristic is reflected by a moderate coupling strength between the AWD and SWDIS from June 2010 to December 2013 in the entire NEB (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…This water is stored not only in the surface layer but also in the root-zone layer [26]. Although some studies have demonstrated the presence of a strong correlation between the content of moisture in surface and root-zone [67,82], the coupling strength among soil layers decreases as depth increases, and moreover depend on the prevailing hydrometeorological conditions [36,83,84].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations